Zygmunt Mycielski – Michał Bristiger. Dialogi z Andrzejem Panufnikiem i socrealizmem w tle - Klubiński, Michał (Res Facta Nova, 2021)
The paper is focused on analysing three texts: a letter from Zygmunt Mycielski to Michal Bristiger dated 15/16 March 1954, the latter’s answer from the beginning of April 1954, and Michal Bristiger’s article in Przegląd Kulturalny titled Andrzej Panufnik. Rozważania bez hagiografii [Andrzej Panufnik. Reflections without hagiography] which is the subject of the correspondence. The main topic of this dialogue is the question whether Panufnik’s oeuvre is grounded in socialist realist doctrine and whether the composer and his work were victimised by the communist system. In the paper the author also analyses the neoclassical views of the composers, Panufnik and Mycielski, and examines one of their strategies – relating to the great European traditions and re-defining the aims of socialist realism by promoting folklore.